1996
DOI: 10.1007/bf00185990
|View full text |Cite
|
Sign up to set email alerts
|

Chondrogenic cell subpopulation of chick embryonic calvarium: isolation by peanut agglutinin affinity chromatography and in vitro characterization

Abstract: The embryonic skull bone, the calvarium, develops via intramembranous ossification, whereby mesenchymal cells differentiate directly into osteoblasts. However, under certain conditions, such as systemic calcium deficiency, regions of cartilage-like tissue are observed in the chick embryonic calvarium, suggesting the presence of pre-cartilage cells. We have recently identified and isolated a chondrogenic cell subpopulation from chick embryonic calvarium by Percoll gradient centrifugation. Using peanut agglutini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 58 publications
0
19
0
Order By: Relevance
“…3,40 After chondrogenic differentiation, these cells no longer are able to bind PNA, further illustrating the utility of PNA binding as a method for identifying precartilage cells. In fact, affinity chromatography to fractionate PNA-binding cells results in a cell population with enhanced chondrogenic ability, 91,92 suggesting that PNA is possibly a functional marker for chondroprogenitor cells. Currently, there is no information on what other cell-surface characteristics best define an embryonic chondrogenic precursor cell.…”
Section: S106mentioning
confidence: 97%
“…3,40 After chondrogenic differentiation, these cells no longer are able to bind PNA, further illustrating the utility of PNA binding as a method for identifying precartilage cells. In fact, affinity chromatography to fractionate PNA-binding cells results in a cell population with enhanced chondrogenic ability, 91,92 suggesting that PNA is possibly a functional marker for chondroprogenitor cells. Currently, there is no information on what other cell-surface characteristics best define an embryonic chondrogenic precursor cell.…”
Section: S106mentioning
confidence: 97%
“…A number of signaling molecules, including Wnts, transforming growth factor-␤, and Notch, promote the specification of particular cell fates in neural crest cells (36)(37)(38)(39)(40). Other experiments have shown that osteoblastic cells from embryonic calvarial bones have the potential to differentiate into chondrocytes in vitro (41)(42)(43), suggesting that there are bipotential progenitor cells in these tissues derived from CNC cells, and that there is a degree of plasticity in the cell fate determination of these cells.…”
Section: Sox9 Is Needed For the Specification Of Both The Chondrocytementioning
confidence: 99%
“…The osteogenic cell population in mouse bone marrow cultures was found to bind WGA and synthesize bone-specific proteins such as alkaline phosphatase, type I collagen and osteocalcin, and to form mineralized nodules [12]. Peanut agglutininbinding cells with chondrogenic potential were found in the chick embryo calvarium [13]. These lines of evidence all support a functional role of glycoconjugate-binding lectins in morphogenesis.…”
Section: Introductionmentioning
confidence: 92%